Utilizing gravity in movement-based games and play - Hämäläinen, Perttu; Marshall, Joe; Kajastila, Raine; Byrne, Richard; Mueller, Florian ‘Floyd’ (2015)
This paper seeks to expand the understanding of gravity as a powerful but underexplored design resource for movement-based games and play. We examine how gravity has been utilized and manipulated in digital, physical, and mixed reality games and sports, considering five central and gravity-related facets of user experience: realism, affect, challenge, movement diversity, and sociality. For each facet, we suggest new directions for expanding the field of movement-based games and play, for example through novel combinations of physical and digital elements.